Preparedness of the Healthcare Personnel Against the Coronavirus Disease 2019 (COVID-19) Outbreak: An Audit Cycle - Zafar, Nowera; Jamal, Zohaib; Mujeeb Khan, Muhammad (Frontiers in Public Health, 2020)
With the increasing spread and mortality of the COVID-19 (Coronavirus disease 2019) pandemic, it is essential for the healthcare community to be prepared per the international standards. This study is focused on assessing the preparedness of healthcare personnel and the effectiveness of an educational intervention to improve this preparedness in those dealing with the COVID-19 infection. A prospective, multicenter audit cycle was conducted on 400 healthcare professionals (271 junior doctors, 90 nurses, 39 non-clinical hospital workers) sampled through stratified random sampling. A questionnaire that was based on 'Centers for Disease Control and Prevention (CDC)’s checklist for healthcare personnel’s preparedness for transport and arrival of patients with confirmed or possible COVID-19’ was sent to the participants after which an informative document, framed on the information provided by World Health Organization (WHO), CDC and local guidelines from the Government of Pakistan's website, was distributed through social media platforms. The questionnaire was repeated after two weeks to close the audit loop. Chi-Square test and paired sample t-test were used to test significance. In the pre-intervention portion of the study, it was found out that the doctors and nurses had higher knowledge scores compared to the nonclinical hospital staff (p-value≤0.05). A statistically significant improvement was seen after the educational intervention was deployed (p-value≤0.05). The study concludes that the nonclinical staff, being a vital part of the healthcare framework, need to be educated and effective approaches for official inclusion of relevant information need to be incorporated into clinical practice to limit the transmission of COVID-19.